2022
DOI: 10.1186/s12957-022-02790-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an extended Cox prognostic model for patients with ER/PR+ and HER2− breast cancer: a retrospective cohort study

Abstract: Background The purpose of this study was to explore a new estrogen receptor (ER) and/or progesterone receptor (PR)+ and human epidermal growth factor receptor 2 (HER2)− breast cancer prognostic model, called the extended Cox prognostic model, for determining the cutoff values for multiple continuous prognostic factors and their interaction via the new model concept and variable selection method. Methods A total of 335 patients with ER/PR+ and HER2−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
1
1
1
Order By: Relevance
“…Fujii et al [ 41 ] found that a pre-NAC ER threshold of 10% is a better cut-off for distinguishing ER-positive from ER-negative breast cancer than 1%, but this threshold is based on speculation only and has not been statistically analyzed. In our study, PR was not an independent predictor of patient DFS, which is inconsistent with previous studies [ 30 , 42 ]. We speculate that this situation may be due to the interaction between ER and PR and the different study populations included.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Fujii et al [ 41 ] found that a pre-NAC ER threshold of 10% is a better cut-off for distinguishing ER-positive from ER-negative breast cancer than 1%, but this threshold is based on speculation only and has not been statistically analyzed. In our study, PR was not an independent predictor of patient DFS, which is inconsistent with previous studies [ 30 , 42 ]. We speculate that this situation may be due to the interaction between ER and PR and the different study populations included.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we discovered that the clinical N stage, ER, Ki67, and p53 were linked to patient DFS results (either pre- or post-NAC ER, Ki67, and p53), which is consistent with previous reports showing that ER expression is a favorable prognostic factor, and lymph node positivity and increased Ki67 and p53 markers have been linked to a worse prognosis [ 15 , 30 , 31 , 32 , 33 , 34 ], but previous studies lacked exploration in the context of NAC for breast cancer conditions. In this condition, the impact of changes in biomarkers such as ER levels during chemotherapy also needs to be considered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation